Giving in a large economy: price vs. non-price effects in a field experiment - Diederich, Johannes; Goeschl, Timo (Discussion paper series, 2011)
We conduct a large-scale field experiment with 2,440 subjects in which we exogenously vary the price of contributing to the closest empirical counterpart of an infinitely large public good, climate change mitigation. We find that the price effect is robust and negative, but quantitatively weak, with a price elasticity of -0.25. Socioeconomic variables such as education, situational variables such as meteorological conditions around the time of the experiment, and attitudinal variables that can be linked to guilt and moral responsibility dominate the price effect. The latter also explain better than price arbitrage the decision of subjects to declare to be field price censored. The results provide an experimental window on the absolute and relative role of price effects on public goods contributions in a large economy and inform current attempts to build a coherent theory of charitable giving.